2021
DOI: 10.3390/mi12070788
|View full text |Cite
|
Sign up to set email alerts
|

Current Stimulation of the Midbrain Nucleus in Pigeons for Avian Flight Control

Abstract: A number of research attempts to understand and modulate sensory and motor skills that are beyond the capability of humans have been underway. They have mainly been expounded in rodent models, where numerous reports of controlling movement to reach target locations by brain stimulation have been achieved. However, in the case of birds, although basic research on movement control has been conducted, the brain nuclei that are triggering these movements have yet to be established. In order to fully control flight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The mammalian amygdala initiates predation behavior and affects the expression of appetite behavior 21 , 22 . Till date, limited studies have examined the role of the amygdala in the expression of motor behaviors in birds, and existing studies have shown that the amygdala mediate distinct aspects of appetitive extinction learning 23 , and TnA could induce right and left body turns in pigeon 24 . The role of PoA in the regulation of motor behavior is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian amygdala initiates predation behavior and affects the expression of appetite behavior 21 , 22 . Till date, limited studies have examined the role of the amygdala in the expression of motor behaviors in birds, and existing studies have shown that the amygdala mediate distinct aspects of appetitive extinction learning 23 , and TnA could induce right and left body turns in pigeon 24 . The role of PoA in the regulation of motor behavior is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The third is the category targeted in the midbrain motor regions responsible for coordinating the movement process to directly control motion. These numerous related nuclei include torus semicircularis (ToS) [39], nucleus intercollicularis (ICo) [10,39], substantia grisea et fibrosa periventricularis (SGP) [39][40][41], formatio reticularismedialis mesencephali (FRM) [11], locus ceruleus (LoC) [10], as well as the nucleus rotundus (RT), tractus occipitomesencephalicus (OM), nucleus taeniae (TN), tractus septo-mesencephalicus (TSM), and archistriatum ventral (AV) [18]. The stimulation-based control targeted in the midbrain motor regions bypasses the complex upward processes of information integration, judgment, and motion planning decision-making, significantly reducing potential interference during the control [10].…”
Section: Midbrain Motor Regionsmentioning
confidence: 99%
“…The role of the state perception module is to obtain real-time status of pigeons, to execute control of the current position, posture, or neural dynamic information. For indoor control tasks, existing research mainly relies on real-time position information recorded by motion tracking systems [18] or visual observations of pigeon behavior by operators [12]. In outdoor open environments, especially in long-distance control tasks, most studies choose to use a global positioning system (GPS) to obtain real-time position status of pigeons [6,42] to overcome the limitation of the infeasible visual observation and the difficult construction of motion capture systems.…”
Section: The State Perception Modulementioning
confidence: 99%
See 1 more Smart Citation
“…Small animal robots exhibit outstanding adaptability to diverse application scenarios, can achieve effectively autonomous obstacle avoidance in complex environments, and can mitigate against external interference, making them a popular choice for disaster relief and topographic surveys [16][17][18][19][20]. Animal robots have become a highly anticipated frontier field, and the research on pigeon robots is also in full swing [15,[21][22][23][24]. At present, the research on pigeon robots is facing a bottleneck, and it is still difficult to realize the fine control of the flight action of it through the brain-computer interface.…”
Section: Introductionmentioning
confidence: 99%